Salingwika an English-to-Filipino machine translator - Basilio, Joanne S.; Cunanan, Johanna D.; Dorin, Leah Wee S.; Lim, Symonette R. (1999)
Communication is one of the most important aspects of any relationship. More often than not, conflicts and arguments occur because of the lack or misuse of it. Even if both sides have the best of intentions, husbands and wives still get into arguments, best friends still turn into bitter rivals, and nations still become hostile to one another. All because they failed to understand what the other side was saying! Thus, for progress to happen in this age of global economies and ever increasing trade, we must learn to communicate effectively. The language barrier should not be a hindrance to effective communication. Though English may come as a second language to some Filipinos, there are those who are more capable and who are more efficient when using the Filipino language. In addition, the current trend in elementary education of emphasizing the vernacular and de-emphasizing English in the classromms is most likely to increase the demand for Filipino translations of textbooks, stories and novels originally written in English. Our project is a computerized machine translator that aims to implement the translation of English texts into Filipino. Using the grammatical and syntactical tools of both languages, the translator aims to restate an English sentence into its grammatically, syntactically and semantically correct Filipino equivalent. In this case, the source language of the machine translator is English and the target language is Filipino. Usually, when an ordinary person proficient in both languages tries to translate a sentence from one language to another, he or she follows a set of implicit and explicit grammar rules. Aside from the grammar rules, such as putting a subject before the verb or vice versa, one also has to take note of the meaning, or semantics, of the word. It is not just a clear case of translating one English word to its direct Filipino equivalent. In our minds, we follow many implicit and intuitive translation rules that cannot easily be explicitly explained and enumerated. There are rules, but there are also many exceptions to the rules. This vagueness has made it difficult for present machine translator programs to come up with a coherent translation. It is this problem that our project aims to address. The presence of an English-to-Filipino translator would greatly benefit those who have poor English comprehension and those who are not able to comprehend the language. Their lack of skills in English would no longer hamper them from understanding what an English speaker might be saying. At a time when English is the primary language of business and economics, this would be of help to an increasingly Filipino speaking population.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Text, translation, computational processing; English-Filipino translator; Translation engine; Salingwika (Computer program).